2015
DOI: 10.1016/j.neuroimage.2014.12.011
|View full text |Cite
|
Sign up to set email alerts
|

How number line estimation skills relate to neural activations in single digit subtraction problems

Abstract: The Number Line (NL) task requires judging the relative numerical magnitude of a number and estimating its value spatially on a continuous line. Children's skill on this task has been shown to correlate with and predict future mathematical competence. Neurofunctionally, this task has been shown to rely on brain regions involved in numerical processing. However, there is no direct evidence that performance on the NL task is related to brain areas recruited during arithmetical processing and that these areas are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 93 publications
(190 reference statements)
0
25
0
3
Order By: Relevance
“…A developmental study ( Sasanguie et al, 2012 ) found that when mathematical ability was tested with complex problems, the number line estimation ability predicted performance more strongly than the number comparison ability. Previous neuroimaging studies for children have demonstrated that complex arithmetic problem activates the parietal lobe more than simple arithmetic problem ( Menon et al, 2000 ; De Smedt et al, 2011 ; Ashkenazi et al, 2012 ; Berteletti et al, 2015 ). Moreover, the number line estimation ability has significant correlations with complex arithmetic performance in the brain.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…A developmental study ( Sasanguie et al, 2012 ) found that when mathematical ability was tested with complex problems, the number line estimation ability predicted performance more strongly than the number comparison ability. Previous neuroimaging studies for children have demonstrated that complex arithmetic problem activates the parietal lobe more than simple arithmetic problem ( Menon et al, 2000 ; De Smedt et al, 2011 ; Ashkenazi et al, 2012 ; Berteletti et al, 2015 ). Moreover, the number line estimation ability has significant correlations with complex arithmetic performance in the brain.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, the number line estimation ability has significant correlations with complex arithmetic performance in the brain. One neuroimaging study showed that number line estimation ability was related to arithmetic performance by comparing the activation of the parietal lobe for simple and complex arithmetic problems ( Berteletti et al, 2015 ). A training study showed that less activation occurred in the parietal lobe in response to a number task following number line estimation training ( Kucian et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, a standard approach is to explore the relationship between outside‐the‐scanner behavioral measures and patterns of brain activity (so‐called “brain–behavior relations”). This approach includes cross‐sectional comparisons, such as contrasting activity patterns between children with and without mathematical learning disabilities (Price, Holloway, Rasanen, Vesterinen, & Ansari, ; Rosenberg‐Lee et al, ) or between children versus adults (Ansari & Dhital, ; Kawashima et al, ), and individual difference designs that involve correlating brain responses with participant age (Rivera, Reiss, Eckert, & Menon, ) or a math‐relevant skill measured outside the scanner (Berteletti, Man, & Booth, ; Metcalfe, Ashkenazi, Rosenberg‐Lee, & Menon, ). Notably, these sorts of “neural correlates” analyses are fairly straightforward in most neuroimaging software platforms, likely contributing to their ubiquity.…”
Section: Using Training Studies To Ask Causal Questions About Brain Amentioning
confidence: 99%